Neurotensin(8-13) analogs targeting NTS1 and NTS2 receptors: A comparative in vitro and molecular modeling study - Kiril Kirilov; Maria Ponticelli; Toni Kühl; Harald Hübner; Maya G. Georgieva; Matthias Vogel; Aneliya A. Balacheva; Bodo Haas; Tamara I. Pajpanova; Maima Matin; Luigi Milella; Peter Gmeiner; et al. (Current Research in Biotechnology)
The simultaneous activation of both neurotensin type 1 and 2 receptors (NTS1R and NTS2R) through the neuronal peptide neurotensin (NT), activating the dopamine (DA) release and DA signaling within the dopaminergic system in the brain, suggest that NTS1R/NTS2R dual-specific NT analogs may represent an attractive tool in the treatment of Parkinson’s disease (PD) and/or other related conditions. Herein, we report in silico exploration of NTS1R and NTS2R driven by in vitro pharmacological evaluation of the linear hexapeptide NT analogs 3 (sequence Lys8-Cav9-Pro10-Tyr11-Ile12-Leu13) and 6 (Arg8-Cav9-Pro10-Tyr11-Ile12-Leu13), both active towards the human NTS1R and NTS2R. Compared to the parent peptide NT(8–13) (2), compounds 3 and 6 showed improved in vitro human plasma stability and BBB permeability. Moreover, in silico ADMET evaluation indicated that both NT-analogs have strong pharmacological properties combined with good safety profiles, highlighting their potential for further structural improvements. Furthermore, we applied an AI-based approach to generate the homology models of hNTS1R and hNTS2R, followed by MD simulations of their ligand-free state and molecular docking in order to estimate the most probable protein–ligand complexes of peptides 3 and 6. Binding interaction/affinity analysis of the best-ranked docking modes, obtained with selected time-frames from the respective MD trajectories, suggest that the receptor activation occurs via a ligand-receptor binding into the initial “entry” conformation of hNTS1R and hNTS2R. This assumption is supported by additional HYDE analysis confirming the binding affinities of peptides 3 and 6 towards hNTS1R and hNTS2R obtained by radioligand binding experiments. The reported study may serve as a ready-to-use in silico approach for further development of therapeutic options against PD and potentially other neurological disorders.